Prenatal alcohol exposure and the early neurodevelopmental outcomes of children in a South African birth cohort study - Hendricks, Gaironeesa (Department of Psychiatry and Mental Health, 2021)
Introduction: Over the last few decades, prenatal alcohol exposure (PAE) has been a major public health problem both globally and in low- to-middle-income countries (LMICs) such as South Africa. Pregnant women and new mothers are particularly vulnerable; and PAE may be associated with adverse child neurodevelopmental outcomes. However, few studies have explored the association of PAE, including risk factors, and subsequent neurodevelopmental trajectories over multiple timepoints in the early years. Given the high burden of PAE and associated risk factors, and the relative paucity of empirical data, further work in South African populations is warranted. This thesis aimed to investigate the association between PAE and early neurodevelopmental outcomes in the Drakenstein Child Health Study (DCHS), a South African birth cohort. The specific objectives included: 1. a systematic review on the available longitudinal studies exploring the impact of PAE on language, speech and communication development (Chapter 3 Manuscript 1); 2. an exploration of the association between PAE and motor, language and cognitive outcomes in infancy (Chapter 4- Manuscript 2); 3. an investigation of the association between PAE, including interactions of tobacco smoking exposure, and the neurodevelopmental trajectories (motor, language and cognitive outcomes) of children across the first 4 years of life (Chapter 5 Manuscript 3); 4. a comparison of the conversational turn-taking between mothers and their alcohol exposed children compared to those between mothers and their unexposed children (Chapter 6 Manuscript 4). Methods: This thesis included four publications, three of which present data from the DCHS. Pregnant women were enrolled from two public primary healthcare clinics, Mbekweni (a predominantly black African population) and TC Newman (a mixed-ancestry population), and more than 1000 mother-child dyads were followed longitudinally from birth through the first 5 years of life. For this study, both antenatal and postnatal maternal measures were used to assess moderate-to-severe levels of PAE. These measures included the (i) Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) antenatally, (ii) a retrospective alcohol questionnaire in the postnatal period at 3-6 weeks and/or 24 months testing age. At 6, 24 and 42 months, early neurodevelopmental outcomes were assessed using the Bayley-III Scales of Infant Development (BSID-III), the Kaufman Assessment Battery for Children (KABC-II) or the Peabody Picture Vocabulary Test (PPVT-IV). Conversational turn-taking in mother-child dyads was also assessed at 42 months testing age. Both univariate and multivariate analyses were used to analyse the data. Results: The findings of this thesisshowed that PAE was significantly associated with both fine motor (B=-3.30, 95%CI 0.06-0.46, p=0.001) and gross motor scores (B=-0.30, 95%CI 0.06-0.44 p=0.001) at 6 months (Chapter 4 Manuscript 2). Chapter 5 (Manuscript 3) showed that when accounting for the interaction between prenatal alcohol and tobacco smoking exposure, impaired fine motor functioning occurred up till 24 months (B=-12.59, 95%CI -21.98- -3.19, p=0.01), but these effects attenuated by 42 months. Significant interactions occurred between prenatal alcohol, including tobacco smoking exposure, and impaired receptive vocabulary (B=-2.49, 95%CI -5.24 -0.27, p=0.02) and cognitive functioning at 24 months (B=- 3.25, 95%CI -5.98- -0.52, p=0.02) (Chapter 5 Manuscript 3). Finally, when exploring conversational turn-taking in alcohol exposed mother-child dyads and unexposed dyads, PAE was significantly associated with conversational turn-taking i.e. child overlapping utterances (OR=3.25, CI 0.98-10.76, p=0.050) (Chapter 6 Manuscript 4). Conclusion: The associations of PAE with early neurodevelopmental outcomes shown here expand on the previous literature. Our findings reported that PAE may influence early neurodevelopmental outcomes, however, future studies should include additional longitudinal studies to replicate the findings, and ongoing follow-up of our own cohort may continue clarify the potential association of PAE and additional risk factors on later neurodevelopmental outcomes at school age and beyond. Effective alcohol programmes targeting pregnant women and interventions to address child developmental impairments in this vulnerable cohort are required.